Implementation status on institutional CRIS/RIM systems in Peru: Integration between the national peruCRIS and institutional CRIS systems - Alhuay Quispe, Joel; Velarde Gutierrez, Renato; Peña Pineda, Karla; Bautista Ynofuente, Lourdes (euroCRIS, 2025)
Extended abstract to be presented at the Spring 2025 euroCRIS membership meeting in Leuven